ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DENGAN BANK KONVENSIONAL SEBELUM DAN SETELAH KRISIS GLOBAL 2008 - Renny Mointi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
This study aimed to analyze the differences in performance of Bank Muamalat and Bank Bukopin before and after the 2008 global crisis. The analysis method used is the method of analysis Parief Samples T test (t test) with data processing using the Statistics Program For Social Sience (SPSS) version 16.0. The results of this research show that there are significant differences between the performance of Bank Muamalat and Bank Bukopin before and after the 2008 global crisis. Before the global crisis), 2007) the performance of Bank Muamalat average of 25.29, while the average Bukopin 22.14. After the global crisis (2009) the performance of Bank Muamalat has decreased on average by 2.28 to 83.00, while the financial performance Bukopin decreased on average by 1.00 to 21.14.